Academic engagement, Locus of Control and School Performance in university students - Mora-Romo, José Fernando; Martell-Muñoz, Juan; Nuñez, Alejandro (Perspectivas en Psicología, 2025)
Introduction: The aim of this study was a) to identify the relationships between Academic Engagement (AE), Locus of Control (LoC) and School Performance (SP), b) to analyze the differences between academic engagement and locus of control, and c) analyze the differences between these variables in university students from three different undergraduate academic departments (e.g. Psychology, Law, and Accounting and Administration). Method: We used a non-probabilistic sample of 362 students, with a mean age of 20.87 years (SD = 2.70), distributed in three different undergraduate departments (Psychology n = 112, Law n = 124, and Accounting and Administration n = 125), who answered the Academic Engagement Scale, the Locus of Control Scale and reported their School Performance through their overall grades. Results: Descriptive analysis, correlations, t-Student and Analysis of Variance (ANOVA) with Tukey post-hoc test were performed with the total sample and separately for the students of each faculty department. The results showed correlations between AE with SP and LoC. The t-Student t-test showed significant differences between the level of AE and the type of LoC that predominated in the students (Internal vs. External). The ANOVA showed differences between students from different faculties in terms of their level of AE, socioeducative interaction and LoC. Conclussions: The implications of AE as a variable associated with SP are discussed, with emphasis on specific factors such as Socioeducative Interaction, Involvement, Academic Performance and Resilience; as well as the effect of the type of LoC on the development of AE.